Climate Change and Violent Conflict in the Sahel and Lake Chad Basin - Kazeem, Olayinka Sodik (Journal of Contemporary International Relations and Diplomacy, 2024)
The purpose of this article is to analyse how climate change is a major threat to security in the Sahel and Lake Chad basin. The region is already experiencing the effects of climate change, such as more frequent droughts, floods, and desertification and to expatiate how these effects are leading to food insecurity, water scarcity, and displacement, which are in turn creating conditions that can lead to violent conflict, using the descriptive cum exploratory research design. The paper relied on qualitative data collected from secondary sources. Findings in the paper revealed that, the link between climate change and violent conflict is complex and there are many other factors that contribute to conflict in the region. However, climate change is a major threat that can exacerbate existing tensions and make it more difficult to resolve conflicts peacefully. The paper recommended measures to address the threat of climate change and violent conflict in the Sahel and Lake Chad basin, it is important to take a comprehensive approach that addresses both the root causes of conflict and the effects of climate change: investing in sustainable development and climate adaptation programme, promoting peacebuilding and conflict resolution, providing humanitarian assistance to those affected by climate change and building the resilience of communities to the effects of climate change, by taking a comprehensive approach, which is possible to mitigate the threat of climate change and violent conflict in the Sahel and Lake Chad basin to build a more peaceful and sustainable future for the region.